ANALISIS PENGARUH TRANSAKSI ONLINE DALAM HUKUM PERLINDUNGAN HUKUM KONSUMEN DIERA DIGITAL - Laila Syahrani; Ika Juwita Lubis (Jurnal Al Wadiah, 2023)
Consumer protection is an important aspect in a country's legal system which aims to protect the rights and interests of consumers in transactions. Consumer protection laws provide the legal basis for protecting consumers from commercial practices that may harm and interfere with consumers' health, safety, or other rights. One aspect that is closely related to consumer protection is legal responsibility for producer negligence and errors. Producer negligence or errors can harm consumers and give rise to legal responsibility for producers. In this context, consumer protection law plays a very important role in determining standards and responsibilities of producers for the products they produce. Therefore, the aim of this research is to investigate the impact of consumer protection laws on the liability of manufacturers in the event of negligence or production defects. It is important to understand that consumers have the right to receive safe and quality products. Consumer protection laws establish minimum standards that must be met by manufacturers in order for their products to be considered suitable and safe. If manufacturers do not meet these standards, consumers have the right to demand compensation and incur legal liability for the producer. In addition, the concept of manufacturer negligence is also the focus of this research. Manufacturer negligence can include various aspects such as poor design, inadequate information, or failure to provide warnings regarding risks associated with the product. Consumer protection law serves to determine whether manufacturers have breached their obligations to consumers and whether consumers are entitled to compensation for losses suffered. Take a deeper look at the impact of consumer protection law on manufacturers' liability for negligence and production defects to better understand how consumers are protected can impact the manufacturer's business practices. We hope that you will gain a deeper understanding and increase your awareness of consumer rights in the legal context. This study is also expected to contribute to a deeper understanding of the development of consumer protection law and the dynamics of consumer-producer relations within the legal framework.